Effect of Third-Generation Beta Blockers on Weight Loss in a Population of Overweight-Obese Subjects in a Controlled Dietary Regimen. (24th September 2021) - Gammone, Maria Alessandra; Efthymakis, Konstantinos; D'Orazio, Nicolantonio
Abstract : Background . Overweight and obesity often develop in individuals with genetic susceptibility and concomitant risk factors; however, medications can represent precipitating factors in some cases: evidence suggests that some antihypertensive drugs can adversely affect energy homeostasis and metabolism. Aim . The primary aim of this study was to investigate whether long-term therapy with a beta blocker impairs weight loss during a period of appropriate personalized hypocaloric diet and standardized physical activity in overweight and obese hypertensive patients in monotherapy and without comorbidities, compared to other antihypertensive drugs and to a control group not taking antihypertensive therapy. Subjects and Methods . We enrolled overweight and obese patients taking antihypertensive drugs; subjects were divided into 3 groups: those taking traditional beta blockers (bB group), those taking third-generation beta blockers (bB-3 group), and those taking other antihypertensive drugs (non-bB group). We also enrolled subjects receiving neither antihypertensive therapy nor other chronic medication in the prior 12 months as controls. All subjects underwent personalized hypocaloric diets for a period of 24 months with monthly follow-up. Anthropometric parameters were measured at enrollment and then monthly after diet prescription. Glucose and lipid values were assessed at baseline and at 12 and 24 months during dietary regimen. Results . We enrolled a total of 120 overweight and obese patients aged 50.30 ± 1.13 years (mean ± standard deviation) with a mean BMI of 31.79 ± 0.65 kg/m 2 ; 90 were taking antihypertensive drugs (no comorbidity and no polytherapy), while 30 subjects receiving neither antihypertensive therapy nor other chronic medication in the prior 12 months were considered as controls. After 6 months, the percent total weight loss (TWL%) was lower in the bB group (3.62 ± 1.96 versus 5.27 ± 1.76 in the bB-3 group, versus 5.15 ± 1.30 in the non-bB group, and versus 4.70 ± 0.87 in the control group), as well as their BMI. After 24 months, we kept finding the worst result in the bB group (TWL% = 9.22 ± 2.19 versus 12.79 ± 1.72 in the non-bB group and 12.28 ± 1.97 in the control group) with the best trend in the bB-3 group (TWL% = 16.19 ± 2.67).